Trade-offs between early planting and yellow rust resistance in wheat: Insights from screening experiments in the Indo-Gangetic plain - Farhad, Md; Tripathi, Shashi Bhushan; Singh, Ravi Prakash; Joshi, Arun; Bhati, Pradeep Kumar; Kumar, Uttam (John Wiley & Sons, 2025)
Wheat crops (Triticum aestivum) that are conventionally planted may exhibit susceptibility to yellow rust (YR). However, the disease can be mitigated if the crops are planted earlier than the recommended planting time. A wheat screening experiment was carried out at the Borlaug Institute of South Asia located in Ludhiana, Punjab, India. The purpose of the study was to gain a deeper understanding of the adaptation patterns of early planted wheat. Early planting was found to be more advantageous for production potential, as well as phenology, stature, and physiological traits. In a separate experiment, each year, the same number of genotypes were screened for YR by artificially inoculating them with pathogen spores. The well-adapted genotypes for early establishment tend to possess a greater vulnerability to YR infection. Furthermore, the infection type score for the genotype selected for early planting showed a significantly greater proportion of S (susceptible) type reactions than for the genotypes adapted to early planting. Intriguingly, more R (resistant) and moderately resistant types of reactions were observed in early-adapted genotypes than in timely-adapted ones. Therefore, further concentrated research on YR screening is required to assess the possibility of breeding early sown wheat in the northwest part of the Indo-Gangetic region.